Knockdown of Bardet-Biedl Syndrome Gene BBS9/PTHB1 Leads to Cilia Defects - Veleri, Shobi (Public Library of Science, 2012)
Bardet-Biedl Syndrome (BBS, MIM#209900) is a genetically heterogeneous disorder with pleiotropic phenotypes that include retinopathy, mental retardation, obesity and renal abnormalities. Of the 15 genes identified so far, seven encode core proteins that form a stable complex called BBSome, which is implicated in trafficking of proteins to cilia. Though BBS9 (also known as PTHB1) is reportedly a component of BBSome, its direct function has not yet been elucidated. Using zebrafish as a model, we show that knockdown of bbs9 with specific antisense morpholinos leads to developmental abnormalities in retina and brain including hydrocephaly that are consistent with the core phenotypes observed in syndromic ciliopathies. Knockdown of bbs9 also causes reduced number and length of cilia in Kupffer's vesicle. We also demonstrate that an orthologous human BBS9 mRNA, but not one carrying a missense mutation identified in BBS patients, can rescue the bbs9 morphant phenotype. Consistent with these findings, knockdown of Bbs9 in mouse IMCD3 cells results in the absence of cilia. Our studies suggest a key conserved role of BBS9 in biogenesis and/or function of cilia in zebrafish and mammals.